ANALYSIS OF RETINAL NERVE FIBER AND GANGLION CELL COMPLEX STATUS IN EARLY OPHTHALMOLOGICAL MANIFESTATIONS OF TYPE 2 DIABETES MELLITUS USING OPTICAL COHERENCE TOMOGRAPHY - Navruzova Dilshoda Tolibovna (World Scientific Research Journal, 2025)
Annotation. This article examines the application of artificial intelligence (AI) in the analysis of ultrasound images in obstetrics, modern algorithms, and their significance in clinical practice. AI technologies allow automating fetal biometric measurements, detecting pathologies, and monitoring fetal condition in real time. The article analyzes the advantages, problems, and promising directions of AI-based approaches.